Acceptance and integration of biofortified vitamin A maize into common diets in northern Zambia - Mulungu, Kevin; Herrington, Caitlin (International Food Policy Research Institute, 2016)
In 2014, a utilization survey was conducted by HarvestPlus among Zambian households belonging to the Livelihood Enhancement Groups (LEGs) that participated in the cultivation of Vitamin A maize (VAM) in the Northern Province. After the first year in which the community was introduced to the biofortified VAM, LEGs grew the crop in group plots, shared produce from the harvest, and participated in their first home-use testing. Nintey-six of the households that cultivated and shared produce were randomly sampled to answer a range of questions. Sampled households included 52 in the Mbala district and 44 in the Luwingu district; The integration of VAM into common diets was assessed through descriptive analysis. Almost all households preferred VAM to both cassava and white maize meal. There were no differences in the likability of VAM across districts or genders. The reasons cited for VAM preference include: nutritional content, taste, and the ability to prepare nshima using less VAM flour compared to cassava and white maize flour. Farmers also liked the agronomic traits of VAM, such as their early maturing and double-cobbing characteristics. These results provide a mix of agronomic and consumption attributes that can be used to promote VAM in the future. These results can also have further research implications, such as the need to econometrically test households' perceived VAM benefits.